Association Between Retinal Microvascular Metrics Using Optical Coherence Tomography Angiography and Carotid Artery Stenosis in a Chinese Cohort - Xu, Qian; Sun, Hongyi; Yi, Qu (Frontiers in Physiology, 2022)
Objectives: The main aim was to investigate the association between retinal microvascular metrics using optical coherence tomography angiography (OCTA) and carotid artery stenosis (CAS) in an aging Chinese cohort. Methods: In this cross-sectional and observational study, 138 eyes of 138 participants were examined. Indices of the microcirculation measured by OCTA included mean vessel density (VD), skeleton density (SD), vessel diameter index (VDI), fractal dimension (FD) and foveal avascular zone (FAZ) of superficial retinal layer (SRL) and deep retinal layer (DRL), and peripapillary vessel caliber. The correlation of these indices with the carotid atherosclerotic lesions including carotid intima media thickness (CIMT) and common carotid artery (CCA) plaque was assessed. Results: A total 72 of 138 eyes demonstrated an increased (≥1 mm) CIMT, and 32 of the eyes presented common carotid plaques. Macular VD, SD and FD were decreased with increasing CCA caliber diameter (p<0.05, respectively). Superficial and deep macular FD were negatively associated with CIMT as well as the existence of CCA plaques (p<0.05, respectively). Conclusions: Changes in retinal microvasculature accessed by OCTA may be used as one of noninvasive early indicators to monitor asymptomatic CAS.